Pengaruh Modal Kerja, Aset Dan Tarif Pajak Terhadap Laba Pada Perusahaan Manufaktur Sektor Barang Konsumen Non Primer yang Terdaftar di BEI Tahun 2020–2023 - Arditasari, Annisa Oktiviani; Indriastuti, D. Ririn (Teewan Journal Solutions, 2025)
Manufacturing companies in the non-primary consumer goods sector listed on the Indonesia Stock Exchange (IDX) are companies engaged in the production and distribution of secondary goods whose demand tends to fluctuate according to economic conditions and consumer purchasing power. The problem in this study is whether there is an influence of working capital, assets, and tax rates on company profits. The main objective of this study is to determine the significance of the influence of working capital, assets, and tax rates on company profits. The usefulness of this study is useful for academics, financial practitioners, and companies in formulating business and investment strategies. The hypothesis in this study is that there is a significant influence between working capital, assets, and tax rates on company profits in the non-primary consumer goods manufacturing sector listed on the IDX in 2020-2023. This study uses a quantitative method with a multiple linear regression approach in analyzing the effect of working capital, assets, and tax rates on company profits. The data required in this study include the financial statements of manufacturing companies in the non-primary consumer goods sector listed on the IDX for the period 2020-2023, especially data related to working capital, assets, tax rates, and company profits. The data sources used are secondary data, obtained from the company's public financial reports that can be accessed through the official website of the Indonesia Stock Exchange (IDX) as well as relevant literature and journals. The data collection technique is carried out through the documentation method, namely by collecting data from the company's published financial reports. The sampling technique uses the purposive sampling method for 11 companies. The results of the t-test show that working capital has a positive but insignificant effect on company profits, assets have a positive and significant effect, while tax rates have a positive but insignificant effect on company profits. The results of the F Test show that there is a significant effect of working capital, assets, and tax rates on company profits. The results of the calculation of the coefficient of determination obtained an R² value of 0.904 indicating that 90.4% of the variation in company profits can be explained by working capital, assets, and tax rates. Therefore, companies are advised to pay more attention to asset management in order to increase profitability.